Sustainability of dual exploitation (fry and adults) of the fish Semaprochilodus laticeps (Characiformes: Prochilodontidae) in Colombia - Bocanegra-Mora, Joan Stiven; Ajiaco-Martínez, Rosa Elena; Ramírez-Gil, Hernando; Barreto, Carlos Guillermo (Revista de Biología Tropical, 2024)
Introduction: Semaprochilodus laticeps is a freshwater fish species native to the Orinoco Basin that is exploited in Colombia at two different stages of its life cycle: fry (for the ornamental trade) and adults (for the consumer market). This double exploitation of juveniles and adults raises concerns about the population stability of the species. Objective: To evaluate the sustainability of the exploitation of the species in these two life stages. Methods: 1 277 specimens of S. laticeps were sampled between June and December 2017. Population parameters were estimated from length-frequency data using ELEFAN 1 routine of the FISAT II package. Length at first maturity (Lm) and length at maximum yield (Lopt) were determined using the Froese and Binohlan equations. Virtual population analysis was performed based on Jones length cohort analysis. Results: Population parameters were as follows: K = 0.75, L∞ = 53.1 cm LE, Z = 2.92 yr-1, M = 1.24 yr-1 and F = 1.68. Lm was estimated to be 29.6 cm SL and Lopt at 33.4 cm SL. Of note, 96.3 % of the fish caught in the consumer fishery exceeded Lm and 80 % exceeded Lopt. The results of the virtual population analysis suggested that a very low proportion (0.85 %) of the population was caught as fry, possibly due to natural mortality. Conclusions: Based on the results, as no indicators of overexploitation were identified, it is recommended to continue with the dual use of S. laticeps. It is recommended to maintain the existing conservation measures, such as the closed season during the reproductive period, to ensure sustainable fishery exploitation. The results obtained can serve as a reference to analyze the situation of other species currently fished for both the ornamental (fry) and food (adult) markets.